Words indicating to free movement from up to down in the Holy Quran: Semantic lexical study - Hasan, Halgord M. (Al-Adab Journal, 2021)
we mean by free movement, movement from high to low, transforming that potential energy in the body into motion and surrendering it to Earth’s gravity completely. after accurate counting, we find that there are eight roots in the Holy Qur’an that give this meaning, and these roots are (descend-nazala , fall from high place -hawa, fall-waqa’a, breakdown-kharra, fall-saqata, landed-habata, fall-radya, putting dawn-sabba), when we look at these words, we note that most of them are synonyms, and they give the meaning of (fall). we start talking about any of those words by analyzing its lexical significance and investigating its semantic developments, after that and by depending on (the indexed dictionary of the words of the Holy Qur’an - by Muhammad Fu’ad Abd al-Baqi) we mention the number of times this word was mentioned and its derivation, then we will discuss how it came In the Holy Quran. One of the most prominent words indicating free movement from high to low is (descended-nazala), as it was mentioned 293 times with its various derivations, that is, approximately 300 times, and in the second place came the derivatives of the linguistic root (fall from high place- hawa) and it came 38 times, and in the third place came the derivatives of the linguistic root (fall-waqa’a) came 23 times, and in the fourth place we find (breakdown-kharra), and its derivatives were mentioned 12 times, and the word root (fall-saqata) and the word root (landed) ranked fifth, so the presence of each of them was eight In the sixth place, the derivatives of the linguistic root (fall-radya) were mentioned five times.